The ETA receptor blocker LU 135252 prevents chronic transplant nephropathy in the “Fisher to Lewis” model - Orth, Stefan; Odoni, Giulio; Amann, Kerstin; Strzelczyk, Piotr; Raschack, Manfred; Ritz, Eberhard (Journal of the American Society of Nephrology, 1999)
The effect of the orally highly bioavailable and specific endothelin A (ETA) receptor antagonist LU 135252 was assessed in a model of chronic renal allograft nephropathy. Kidneys of Fisher rats were orthotopically grafted to Lewis rats. Fisher autografts and kidneys after uninephrectomy served as controls. All animals received low-dose cyclosporin A (CsA; 1.5 mg/kg body wt) for 10 d after surgery. Allotransplanted animals were then randomized to receive standard diet or a diet designed to deliver 30 mg of LU 135252/kg body wt per d for 35 wk. BP was monitored telemetrically. Treatment with LU 135252 did not affect systolic or diastolic pressure. Indices of glomerulosclerosis (GSI), and tubulointerstitial and vascular damage were measured. Chronic transplant nephropathy was almost completely prevented by LU 135252 compared with untreated allografts or kidneys of uninephrectomized controls, i.e., GSI 0.7 ± 0.12 versus 1.6 ± 0.25 (P < 0.001) versus 0.7 ± 0.06 (P < 0.001). Allograft weight and serum creatinine were significantly lower in treated versus untreated animals. The results are consistent with the notion that ETA receptor-mediated events play a role in the genesis of chronic transplant nephropathy.